Comparison of early tumour-associated versus late deaths in patients with central or >7 cm T4 N0/1 M0 non-small-cell lung-cancer undergoing trimodal treatment: Only few risks left to improve. (October 2020) - Guberina, Nika; Pöttgen, Christoph; Schuler, Martin; Guberina, Maja; Stamatis, Georgios; Plönes, Till; Krebs, Bettina; Metzenmacher, Martin; Theegarten, Dirk; Gauler, Thomas; Jöckel, Karl-Heinz; Darwiche, Kaid; et al.
Abstract: Background: The optimal treatment for patients with locally advanced non-small-cell lung-cancer (NSCLC) cT4 cN0/1 cM0 is still under debate. The purpose of this study was to examine the long-term survival of cT4 cN0/1 cM0 NSCLC patients undergoing induction chemotherapy and concurrent radiochemotherapy before surgery. Methods: All consecutive patients with confirmed NSCLC (cT4 cN0/1 cM0) treated with neoadjuvant chemotherapy, concurrent radiochemotherapy (RT/CTx) (45–46 Gy) and surgical resection between 2000 and 2015 were included. According to the UICC guidelines (8th edition), T4 stage was reanalysed by an expert radiologist. The mediastinal staging was performed by systematic EBUS-TBNA or mediastinoscopy. The primary end-point was overall-survival (OS). The power to detect an increase of early tumour-associated mortality (hazard ratio > 3.5) within the first 5 years after treatment in comparison to late deaths beyond 96 months was >80%. Results: Overall, 67 patients were treated with concurrent RT/CTx. T4 criteria were fulfilled by all patients, and multiple T4 criteria by 53 patients. Seventy percent of patients had an initial PET/CT staging. The median follow-up period was 134 months. OS rates at 2, 5, 10 and 15 years were 83.6 ± 4.5%, 65.4 ± 5.9%, 53.3 ± 6.3% and 36.6 ± 6.8%, respectively. A total of 44.8% of patients achieved a pathologic complete response. In multivariable analysis, ypT category was the most predictive factor. OS at 5 years for ypT0 ( n = 31) was 80.5%, and ypT1 ( n = 11) was 62.5%. Main sites of failure were brain and pulmonary metastases in seven and three patients, respectively. The intercurrent annual death rate was estimated from the survival curve beyond 96 months and was found to be 4.75% (95% CI 2.40–9.27%). No significant increased mortality was observed during the first 5 years (annual death rate: 8.31% [95% CI 5.60–12.24%], hazard-ratio = 1.72 [95% CI 0.81–3.65]). Conclusions: The effectiveness of this trimodality schedule is high in patients with cT4 cN0/1 cM0 NSCLC with excellent local control rates. Considering the annual death rate beyond 8 years of survival as an intercurrent death rate due to comorbidity, this treatment schedule reduces annual mortality to background even in the first 5 years after therapy. Highlights: Neoadjuvant radiochemotherapy in cT4 N0/1 NSCLC associated with ypT0-downstaging of 63%. Patients have overall survival above 80% at 5-years after resection setting a benchmark. Trimodal treatment reduces annual mortality to background even in 5 years post-therapy.